Facial virus inoculations infect vestibular and auditory neurons in rats - Helfferich Frigyes; Lourmet Guillaume; Szabó Éva Rebeka; Boldogkői Zsolt; Palkovits Miklós (Orvos-Egészségügyi Dolgozók Szakszervezete, 2016)
Background and purpose – There is growing evidence for the viral origin of the Bell’s facial palsy, vestibular neuritis and sudden sensorineural hearing loss, however their exact pathophysiology is still unknown. We investigated the possibility of brainstem infections following peripheral viral inoculations in rats. Methods – Pseudorabies virus, a commonly used neurotropic viral retrograde tracer was injected into the nasolabial region of rats. Five and 6 days after injections, infected brainstem nuclei were demonstrated by immunohistochemical techniques. Results – Infected neurons were found in the motor facial, the medial vestibular, and the sensory trigeminal nuclei, as well as in the medial nucleus of the trapezoid body. Conclusion – Pseudorabies virus infects auditory and vestibular sensory neurons in the brainstem through facial inoculation. The possible routes of infections: 1. trans-synaptic spread constituted by facio-vestibular anastomoses: primarily infected motor facial neuron infects neurons in the medial vestibular nucleus, 2. via trigeminal sensory nerves: the sensory trigeminal complex innervated by GABAergic medial vestibular neurons, and 3. one bisynaptical route: infected facial motoneurons may receive indirect input from the medial vestibular nucleus and the trapezoid body via connecting neurons in the sensory trigeminal complex. We may assume that latent infections of these areas may precede the infections of the peripheral organs and the reactivation of the virus exerts the symptoms.